2010
DOI: 10.1080/00029157.2010.10404332
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Clinical Hypnosis in the Digestive Endoscopy: A Multiple Case Report

Abstract: The aim of this study is to evaluate the efficacy and viability of hypnosis before and during a gastrointestinal endoscopy. Six Gastroscopies and 22 colonoscopies were carried out under hypnosis in a group of patients. The patients ranged in age from 20 and 67 years and have a history of previously incomplete and poorly tolerated examinations or expressed an active demand for sedation. For 6 of the patients who underwent a gastroscopy under hypnosis, the procedure was successfully completed, reaching the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Previous investigations show a positive effect of hypnosis on other medical procedures especially in terms of the need for medical sedation [19,[27][28][29]. Hypnosis can reduce the amount of medications needed or even completely replace benzodiazepines [22,[30][31][32].…”
Section: Effect Of Hypnosismentioning
confidence: 99%
“…Previous investigations show a positive effect of hypnosis on other medical procedures especially in terms of the need for medical sedation [19,[27][28][29]. Hypnosis can reduce the amount of medications needed or even completely replace benzodiazepines [22,[30][31][32].…”
Section: Effect Of Hypnosismentioning
confidence: 99%
“…In addition, completeness of colonoscopy was observed in all patients in the successful group as compared with only half of them in the failure group. Dominguez-Ortega et al observed an efficacy of hypnosis used alone in EGD (n = 6) and colonoscopy (n = 22), with a good tolerance reported by the patient in 85% of cases (17). Elkins et al studied the effect of hypnosis in the management of pain and anxiety during colonoscopy performed for colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Other effective methods to decrease patient anxiety and discomfort during colonoscopy are listening to music [14]; hypnosis; and inhalation of nitrous oxide, which improves the patient experience during the procedure and is rapidly eliminated [14,15], minimizing after effects and inconvenience to patients. Although nitrous oxide has not been considered to generate aerosol, this has not been investigated in research studies [16].…”
Section: E986mentioning
confidence: 99%